Effect of N-acetyl cysteine on the quality of blastocyst formation rate using cultured vitrified murine embryos - SIGÜENZA, S.; ÁLVAREZ, I.S.; MATILLA, E. (Journal of the Hellenic Veterinary Medical Society, 2020)
Vitrification is the best method for embryo cryopreservation although it increases endogenous reactive oxygen species (ROS) production. N-acetylcysteine (NAC) a free radical scavenger may be used for reducing ROS toxic effects. The aim of the present study is to investigate potential beneficial effects of NAC on the developmental embryo competence applying different culture conditions in vitrified-warmed 2-cell embryos derived in vivo or in vitro. Thus, 2-cell embryos were vitrified or cultured fresh in presence or absence of 1 mM of NAC during: a) the entire embryo culture, b) for 24 hours with NAC at days 1.5 (G1) or 2.5 (G2) and returned to basal embryo culture (KSOM) or c) cultured in the presence of NAC for 12 hours at day 3.5 (G3). Despite NAC addition to fresh or vitrified embryos produced in vivo or by IVF, blastocyst rates remained unchanged. In vitrified-warmed IU or IVF-derived embryos, total cell number varied when NAC was added at day 1.5 although differences were not significant (60.1 ± 1.9 vs. 59.4 ± 1.3 for IU G1 and control respectively; and 59.3 ± 1.6 and 52.6 ± 3.0 IVF G1 and control respectively; mean cell number ± SEM, p > 0.05). It seems that the embryo culture medium supplementation with 1 mM of NAC in the first day after vitrification of development improves blastocyst quality of murine embryos and does not exert any beneficial effect at oyher culture points.